Antenna systems with a mechanically steerable reflector for low cost and high performance radar applications - Yang,Yueheng (Nanyang Technological University, 2021)
Antennas are critical subsystems for any wireless systems,including wireless com munication and radar systems. Moreover, with the rapid development of elec tronic information, the consumer demand for efficient and reliable electronic de vices is also growing rapidly. Therefore, there is an increasing demand for designing low cost and high-performance microwave radar antenna design for some 360-degree critical surveillance applications. Conventionally, a 360-degree surveillance-microwave-radar antenna would rotate the whole antenna sub-system made from metallic waveguide feed and parabolic reflector for radar beam steering. For a low cost solution of a millimeter wave surveillance radar, this project aims to study a cost-efficitive steerable reflector antenna design with motor control. First, basic theory and designs of antenna are analyzed and discussed. Dipole antenna and slotted waveguide antenna system are specially focused, thus gives the conceptual and theoretical foundation for the following work described in this dissertation. Second, the design of a miniaturized half-wave dipole antenna with enhanced gain is carried out. The designed antenna has a working frequency of 9.89 GHz and the size is reduced by approximately 17.2% while the gain is increased by approximately 25.6% compared with the original antenna. In addition, a reflector is introduced. Major parameters affecting the performance are analyzed and compared. Finally, the final design is described. Third, a single slot waveguide antenna is first designed and optimized and then extended into a slot waveguide antenna array with 10 slots. The designed an tenna has a working frequency of 9.79 GHz, while the main lobe gain of the slot array reaches 8.72 dB, the first sidelobe gain is approximately -7.63 dB, which successfully meet the demand. Moreover, a reflector is introduced into the antenna system and the model of the whole antenna system is then given. Fourth, a mechanically steerable reflector control system is designed. The sys tem is driven by a steeper motor and controlled by a Raspberry Pi. Meanwhile,the system is integrated with the antenna body. The whole system consists of a motor with a steering wheel, a rotating arm, a linking adaptor and a reflec tor which allows the free angle rotation as well as distance adjustment. It is low cost, high performance and easily manufactured, which satisfies the design requirements. Keywords: Dipole antenna, Slot waveguide antenna array, Mechanically steer able reflector, Low-cost High-Performance